The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1517-869220172304162818
|View full text |Cite
|
Sign up to set email alerts
|

Study of Body Image in Professional Dancers: A Systematic Review

Abstract: Body image is multidimensional, dynamic, and entirely linked to the body in motion, which entails relevant bodily concerns in the routine of professional dancers, who need to maintain their body aesthetics constantly. The objective was summarizing the scientific production on the body image of professional dancers and to understand how they perceive it. This review is composed by seven studies that investigated professional dancers of classical ballet, jazz and contemporary dance. The results demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
3
12
1
3
Order By: Relevance
“…Moreover, the authors suggested that in advanced/professional ballet dancers the pressure to get excessively slim physiques leads to greater thinness, self-objectification and, consequently, more negative BI. Furthermore, some authors have mentioned that perfectionism and low self-esteem, are usually found among dancers, which might explain why eating disorders appear to be more prevalent among this group of people (Cardoso et al, 2017;Dantas et al, 2018). This is in line with research in the area finding that dancers have more than twice the risk of developing an eating disorder (Heiland, Murray, & Edley, 2008).…”
Section: Faria Frontini and Antunessupporting
confidence: 56%
“…Moreover, the authors suggested that in advanced/professional ballet dancers the pressure to get excessively slim physiques leads to greater thinness, self-objectification and, consequently, more negative BI. Furthermore, some authors have mentioned that perfectionism and low self-esteem, are usually found among dancers, which might explain why eating disorders appear to be more prevalent among this group of people (Cardoso et al, 2017;Dantas et al, 2018). This is in line with research in the area finding that dancers have more than twice the risk of developing an eating disorder (Heiland, Murray, & Edley, 2008).…”
Section: Faria Frontini and Antunessupporting
confidence: 56%
“…Given the aesthetic nature and demands of dance, body shape concerns are often normalized. Indeed, having a thin body is often idealized within the dance industry, which could lead to greater risk for ED risk factors (e.g., internalization of a thin ideal of beauty; Striegel‐Moore & Bulik, 2007), and the development of psychopathology (e.g., compulsive exercise) (Cardoso, Reis, Marinho, Boing, & Guimarães, 2017; Hidayah & Bariah, 2011). In an order to maintain or reduce their weight, dancers may start overtraining or developing disordered eating attitudes (Bolling & Pinheiro, 2010; Cardoso et al, 2017; Ravaldi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of eating disorders [ 5 , 6 , 7 , 8 ], elevated-risk groups might contain persons whose behavioral patterns feature as definite backgrounds of the future increase of an eating disorder, such as extreme dieting, professional pressure to be skinny, and undue exercise. On these estates, athletes [ 9 , 10 , 11 , 12 , 13 ] and ballet dancers [ 14 , 15 , 16 ] were widely examined to recognize the main associates of the risk of eating disorders. In the past, and still today, professional fashion models are “usually considered” as beautiful women seeking success by using their charm and their own body.…”
Section: Introductionmentioning
confidence: 99%